USING FIREWALLS AS IMPORTANT COMPONENTS OF THE SECURITY SYSTEM FOR WEBSITES AND APPLICATIONS - YATSIUK, SVITLANA; YUNCHYK, VALENTINA; YATSIUK, ANDRII; MULIAR, VADIM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Modern websites and applications face numerous security threats, such as DDoS attacks, SQL injections, and malware. In the context of the ongoing increase in cybercrime, firewalls have become critical components of security systems, providing protection for data and the functionality of web resources. This article examines the role of firewalls in protecting websites and applications, their types, and mechanisms of operation. Firewalls serve as the first line of defense by filtering incoming and outgoing traffic, which helps reduce the risk of unauthorized access. The article analyzes studies demonstrating the effectiveness of firewalls in preventing unauthorized access and mitigating risks associated with cyberattacks. Special attention is given to modern technologies such as Web Application Firewalls (WAF), which specialize in protecting web applications from specific threats, such as XSS (Cross-Site Scripting) and SQL injections. It explores the mechanisms by which WAF analyzes traffic and detects anomalies, as well as their integration capabilities with other security systems. The research also covers the integration of firewalls into the overall security architecture of organizations, examining their interaction with other components of the security system, such as threat detection systems and antivirus software. Key recommendations for enterprises regarding the implementation of firewalls into their infrastructure are provided, emphasizing the need to select appropriate solutions based on business specifics and types of threats. The article underscores the importance of continuous monitoring and updating of firewalls to ensure their effectiveness in a changing cyber landscape, as firewalls are an integral part of the security system for websites and applications, requiring a deep understanding of their functions and mechanisms to effectively counter modern cyber threats.